2008
DOI: 10.1017/s0022215108002636
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of caspase-3 and caspase-8 deregulation in tongue squamous cell carcinoma, based on immunohistochemistry and computerised image analysis

Abstract: Simultaneous deregulation of caspase-8 and -3 is a frequent event in tongue squamous cell carcinoma. Activation of caspase-3, which is predominantly down-regulated, may be a crucial process for induction of apoptosis and response to therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
1
32
1
2
Order By: Relevance
“…Since we did not correlate the expression levels of MCPH1 and CASP3 in OSCC samples, we performed a literature search to find if CASP3 expression has been reported in oral cancer. We found that CASP3 protein has been shown to be downregulated in 79/87 (90.80%) of tongue squamous cell carcinoma [43]. In contrary to this study, overexpression of CASP3 (protein) has been reported in a study using 39 samples of normal oral epithelium and 54 oral squamous cell carcinomas [42].…”
Section: Discussioncontrasting
confidence: 88%
“…Since we did not correlate the expression levels of MCPH1 and CASP3 in OSCC samples, we performed a literature search to find if CASP3 expression has been reported in oral cancer. We found that CASP3 protein has been shown to be downregulated in 79/87 (90.80%) of tongue squamous cell carcinoma [43]. In contrary to this study, overexpression of CASP3 (protein) has been reported in a study using 39 samples of normal oral epithelium and 54 oral squamous cell carcinomas [42].…”
Section: Discussioncontrasting
confidence: 88%
“…Activation of Caspase-3 is a critical event during cell apoptosis, which can be activated by upstream signaling from, for example, Caspase-8 and -9 (Janicke, 2008). However, simultaneous deregulation of Caspase-3 and -8 is a frequent event in tongue squamous cell carcinoma (Andressakis et al, 2008). Activation of Caspase-3, which is predominantly down-regulated, may be a crucial process for induction of apoptosis and response to therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the roles of caspase-3/8/9 in cancer, impaired expression of caspase-8 and caspase-3 can promote tumor formation and progression and treatment resistance in several types of cancer, including oral cancer [14, 15]. However, the expression levels of caspase-8 and caspase-9 are higher in oral squamous carcinoma cells (OSCCs) than in the adjacent normal cells [16].…”
Section: Introductionmentioning
confidence: 99%